Illegal imports of tobacco and tobacco products into Russia from the EAEU countries: assessment and areas of minimization - A. V. Salnikova; D. D. Goryacheva (Вестник университета)
Tobacco and tobacco products are in demand in Russian domestic market, which is characterized by shadow segment growth in recent years. Main share in Russian shadow tobacco market structure is represented by imported and counterfeit products. The article assesses the scale of illegal importation of tobacco and tobacco products into Russia from the Eurasian Economic Union countries (hereinafter – EAEU) in 2018–2022. The authors consider the factors contributing to illegal imports of tobacco products growth from the territories of the EAEU member states. The urgent problems of counteracting violation of the order of tobacco and tobacco products importation from the union states have been identified. Measures aimed at ensuring legality of mutual trade in the goods under consideration within the EAEU and reducing the volume of their illegal import into Russia from the territories of the Union member states have been proposed.